EKSISTENSI ZIRWEN HAZRY DALAM BERKARYA SENI LUKIS - Ibnu Karim Dakoga MNA, Drs. Erfahmi, M.Sn., Drs. Abd. Hafiz, M.Pd. (Serupa The Journal of Art Education, 2016)
The purpose of this study is (1) to explain the existence of Zirwen Hazry in the work of art, (2) explain how Zirwen Hazry maintain existence as a painter in West Sumatra. The method used in this research uses qualitative research. Data obtained using observation, interviews, documentation and browsing the internet on Zirwen Hazry along with his work. Techniques in reducing, presentation and verified in reaching conclusions. Results showed that the existence Zirwen Hazry in the work of art is influenced by several factors: that of social institutions, artists and the public.Kata Kunci: Eksistensi, Seni Lukis